Strategi Pedagang Pasar Kahayan Dalam Meningkatkan Pendapatan Saat Pandemi Di Palangka Raya - Rinto Alexandro; Fendy Hariatama; Yeriana Yeriana (FKIP Universitas Palangka Raya, 2023)
The Kahayan Market in Palangka Raya City is one of the largest markets in Palangka Raya City. The purpose of this study was to determine the income of traders before and during the Covid pandemic. The research approach used is a qualitative approach. This approach is carried out on all research objects so that the data search process can run easily and according to plan. Data sources are divided into two, namely primary data and secondary data. 1) Primary data is data obtained by researchers directly from informants which can be in the form of direct interviews with research informants. Informants in this study are: traders in the Kahayan market, Palangka Raya City. 2) Secondary data or supporting data are data obtained indirectly from the research object. In this study secondary data was obtained by collecting data and retrieving information in the form of documents, the internet, photographs and some literature. Journals that are considered relevant to the research problem. Research Results: Their economy is only supported by income that day. Their income is very low because when they don't work or trade, their income also doesn't exist.